We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
109
2
avatar+62 

2.Let $f(x) = 3x + 2$ and $g(x) = x^2 - 5x - 1.$ Find $f(g(x)).$

 Mar 2, 2019
 #1
avatar+18449 
+1

in 3x+2     put in  x^2-5x-1   for 'x'  and see what you find.....

 Mar 2, 2019
 #2
avatar+101856 
+2

2.Let $f(x) = 3x + 2$ and $g(x) = x^2 - 5x - 1.$ Find $f(g(x)).$

 

f(g(x)  = f(g)    means that we are just subbing    g into   f.....so we have

 

3 ( x^2 - 5x - 1) + 2         simplify

 

3x^2 -15x -3 + 2  =

 

3x^2 -15x  - 1

 

 

cool cool cool

 Mar 2, 2019

7 Online Users